Analisis Strategy Interactive Marketing Pada Produk Tabungan Elemen IFAS dan EFAS Memanfaatkan Metode SWOT - Husni Mubarok; Hendra Lesmana; Bayu Purnama Putra; Azizah Mursyidah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Channeling funds in sharia marketing requires a very mature and accurate strategy because the sales strategy is a consolidated element of the business strategy for sharing the benefits of a management business entity. Actual trade strategy activities in achieving the goals of the institution can be carried out actively, clearly and logically about product brands in a turbulent business. The technique of collecting primary data and secondary data is a mixed method descriptive combination of quantitative and qualitative which aims to determine the elements of IFAS and EFAS by utilizing the SWOT method to determine company strategy. The results of research on PT BSI Tbk product elements IFAS functioning strategy strength opportunities 3.16 minimizing weakness opportunities strategy 2.77 in funding products have good potential in attracting new prospective customers supported by the development of modern market share supported by its sophisticated technology. The EFAS element uses a strategy of strength treaths 3.57 minimizes weakness strategies 3.18 makes it easy for customers to make transactions in cash or non-cash, in interacting marketing employees with customers must be well established and friendly, when customers ask for explanations that are easy to understand by these customers, in promoting and socializing funding products must be understood by ordinary people because there are still many people who do not understand sharia products, the majority of Muslims in Indonesia will be good at developing sharia trends.